Detection and genome sequence of a new betapartitivirus associated with Cucurbitaria piceae Borthw. fungus causing bud blight of spruce in the Czech Republic - Petrzik, Karel; Koloniuk, Igor; Sarkisova, Tatiana; Hrabáková, Lenka (Archives of virology, 2016)
A new bisegmented dsRNA virus has been detected in shoots of blue spruce with bud blight disease symptoms and infection by Cucurbitaria piceae (Bortw.) fungus. The virus genome consists of two segments that are 2071 and 2257 nt long, encoding the putative RNA polymerase and capsid protein, respectively. Rosellinia necatrix partitivirus 1 is a closely related virus with 45 % amino acid sequence identity in the polymerase, and crimson clover cryptic virus 2 has 36 % amino acid sequence identity in the capsid protein. Based on taxonomic criteria, the virus should be classified as a member of the genus Betapartitivirus (family Partitiviridae). The name Cucurbitaria piceae partitivirus 1 and acronym CpPV1 are proposed.
Keywords: Genome, Viral; fylogeneze; mykoviry; Česká republika; Phylogeny; Molecular Sequence Data; molekulární sekvence - údaje; Czech Republic; Base Sequence; výhonky rostlin; Plant Diseases; nemoci rostlin; sekvence aminokyselin; Ascomycota; sekvence nukleotidů; genom virový; Plant Shoots; smrk; Amino Acid Sequence; Fungal Viruses; Picea